Time to peak velocity in the main pulmonary artery as a marker of persistent pulmonary hypertension in neonates. Issue 2 (21st December 2018) - Gately, Callum; Patel, Harshad
Abstract: Purpose: To assess right ventricular systolic time intervals, specifically, time to peak velocity (TPV) in the pulmonary artery as a marker of persistent pulmonary hypertension of the newborn (PPHTN). Methods: This was a retrospective case–control study of 30 infants with pulmonary hypertension requiring intensive care management. Cardiac ultrasounds were re‐analysed, comparing TPV measurements to a group of 31 controls who had cardiac ultrasounds performed for incidental murmurs with structurally normal hearts. Results: Time to peak velocity was significantly shorter in the PPHTN group compared to controls, 47 vs. 95 ms, respectively. This was statistically significant with a P‐value of <0.001. Conclusion: Time to peak velocity in the pulmonary artery is a useful marker of PPHTN in the first week of life. This measurement is especially useful if neither tricuspid regurgitation or a patent ductus are present for interrogation on ultrasound.